The Antibacterial Activity of Certain Sansevieria Thunb. Species against Escherichia coli - Tkachenko, Halyna; Buyun, Lyudmyla; Osadowski, Zbigniew; Maryniuk, Myroslava (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2017)
The present study was aimed to investigate in vitro antimicrobial activity of ethanolic extracts of seventeen species of Sansevieria Thunb. genus (Sansevieria canaliculata Carriere, Sansevieria trifasciata Prain, Sansevieria cylindrica Bojer ex Hook., Sansevieria parva N.E.Br., Sansevieria fischeri (Baker) Marais, Sansevieria kirkii Baker, Sansevieria aethiopica Thunb., Sansevieria metallica Gerome & Labroy, Sansevieria caulescens N.E.Br., Sansevieria francisii Chahin., Sansevieria arborescens Cornu ex Gerome & Labroy, Sansevieria volkensii Gurke, Sansevieria forskaliana (Schult. & Schult.f.) Hepper & J.R.I.Wood, Sansevieria gracilis N.E.Br., Sansevieria hyacinthoides (L.) Druce, Sansevieria roxburghiana Schult. & Schult.f., Sansevieria suffruticosa N.E.Br.) against Escherichia coli (ATCC 25922). The crude extracts were screened for antimicrobial activity using agar disk diffusion method. All the extracts showed variable degree of inhibition against tested bacterium. Therefore, the results revealed the antimicrobial potential of these extracts. In fact, the test organism was susceptible to extracts of Sansevieria kirkii, Sansevieria arborescens, Sansevieria roxburghiana, Sansevieria francisii, Sansevieria forskaliana, Sansevieria cylindrica, Sansevieria trifasciata, Sansevieria canaliculata, Sansevieria caulescens, Sansevieria metallica, Sansevieria aethiopica with diameters of inhibition zone from 12 to 24 mm. Escherichia coli isolate was resistant only to S. hyacinthoides extract and the diameter of zone inhibition around the rest ranged from 8 to 10 mm. Thus, the ethanolic extracts obtained from leaves of Sansevieria kirkii, Sansevieria arborescens, Sansevieria roxburghiana, Sansevieria francisii, Sansevieria forskaliana, Sansevieria cylindrica, Sansevieria trifasciata, Sansevieria canaliculata, Sansevieria caulescens, Sansevieria metallica, Sansevieria aethiopica possess antibacterial potency against Escherichia coli isolates and may be used as natural antiseptics and antimicrobial agents in medicine.